Economic cooperation in the wider Central Asia region - Byrd, William A. (World Bank working paper, 2006)
"This paper lays out the big issues that affect regional cooperation and development in the wider Central Asia region, and analyzes in greater detail areas where there appear to be good prospects for progress in the short run. The paper develops a framework for approaching regional cooperation in the wider Central Asia region, based on identifying and analyzing critical linkages among sectors and explicitly recognizing political obstacles and the corresponding need for political incentives to make progress. Modest, "win-win" initiatives will help build trust and momentum for tackling the more difficult areas, but there may also be opportunities for "bold strokes" to augment and change the distribution of benefits sufficiently to leverage more substantial progress."--Jacket.